Dari Pesantren ke Platform Digital: Dinamika Jejaring Ulama dalam Pengembangan Islam Nusantara - Shoopa Alifiah Salsabil; Saeful Anwar; Iffan Ahmad Gufron; Masykur Masykur (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2026)
This study examines the transformation of Nusantara ulama networks from pesantren-based religious authority toward digital-based religious communication in the development of Islam Nusantara in the contemporary digital era. The research is motivated by the rapid growth of digital media which has reshaped patterns of da’wah, transmission of Islamic knowledge, and religious authority within Muslim society in Indonesia. This study aims to analyze the transformation of ulama networks, explore digital da’wah strategies in strengthening Islam Nusantara, and identify the challenges and opportunities of religious authority in digital spaces. The research employs a qualitative approach through library research combined with descriptive-analytical methods and content analysis. Data were collected from books, scientific journals, academic articles, and relevant digital sources concerning pesantren, digital da’wah, religious authority, and Islam Nusantara. The findings indicate that Nusantara ulama networks have transformed into hybrid religious networks that integrate traditional sanad-based scholarship with digital media platforms. Pesantren and ulama increasingly utilize social media, online learning platforms, podcasts, and digital content to disseminate moderate Islamic values and expand religious communication. However, the digital era also generates challenges, including the fragmentation of religious authority, the rise of influencer-based legitimacy, and the spread of unverified religious content. Despite these challenges, digital media provide significant opportunities for strengthening Islam Nusantara as a moderate, inclusive, and contextual Islamic discourse within global digital society.